VARIABLES USED FOR TALENT IDENTIFICATION AND DEVELOPMENT IN SOCCER: A SCOPING REVIEW (Kinesiology, 2025)
Talent identification and development in youth soccer are complex and multidimensional processes. This scoping review aimed to explore the current literature regarding the variables used in the talent identification and development process in soccer. This study was developed referring to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) guidelines. Pubmed, Web of Science and Scopus databases were searched from September to October 2023. Only peer-reviewed journal articles published in English were included, with no limitation regarding the publication year. Through the initial search 774 records were identified and 190 articles met the inclusion criteria. The main finding was that most studies assessed speed (52.1%), maturity (42.1%), lower limbs strength (40.5%), aerobic capacity (35.8%), agility (32.6%), technical skills (16.8%), and tactical skills (14.2%). Male athletes were investigated in 162 studies (85.3%), whereas seven studies (3.7%) were conducted with females only, and seven articles (3.7%) with males and females. Fourteen studies (7.4%) did not specify the sex of the participants. In conclusion, findings indicate that physical performance and maturity factors are the most investigated variables regarding talent identification and development in soccer. This review highlights the importance of considering physical performance tests and technical/tactical skills, along with maturity status assessment, as key tools in talent identification programs. Current talent identification practices in soccer may benefit from a more balanced approach that includes physical, technical, tactical, maturational, and psychological assessments to capture a broader range of player potential.Key words: young athletes, football, talent, youth development